The toxicology of styrene monomer and its pharmacokinetics and distribution in the rat. - Withey, Jim R. (Scandinavian Journal of Work, Environment & Health, 1978)
The pharmacokinetics of styrene after intravenous administration to rats (at doses ranging from 1.3 to 9.3 mg/kg) yielded dose-dependent kinetics which fit a two-compartment mathematical model. The elimination and distribution coefficients all decreased as the dose increased, but the apparent volume of distribution remained the same. Rapid distribution to the major organs was observed, and qualitative kinetics for the elimination from the heart, liver, lung, spleen, kidney and brain all indicate a kinetic behavior and magnitude similar to that observed for the blood. Five-hour exposures of individual rats to a tmospher es having styrene concentrations of from 50 to 2,000 ppm yielded uptake blood profiles which showed a continued and increasing absorption of styrene, proportional to the styrene concentration, over the entire exposure period. Postexposure elimination followed a dose-dependent two-compartment model, similar to that observed after intravenous administration, although the initial stage of the elimination was more rapid and the terminal stage much slower than observed in the intravenous case. Tissue concentrations of styrene in heart, liver, lung, kidney, spleen, brain, and perirenal fat showed a different pattern of distribution as the dose increased. At all exposure concentrations, the concentration of styrene in the perirenal fat was 10 times that in any organ. At the lowest exposure concentration the kidney registered the highest concentration, while a higher level of styrene was found in liver, brain and kidney as the exposure level increased, and for these tissues the concentration of styrene was always greater than that in the blood. The pharmacokinetics of styrene after intragastric dosing were dependent on the dosing vehicle. For aqueous solutions a very rapid uptake stage was observed (peak concentrations being observed at <4 min), while solutions in vegetable oil showed a slower and delayed absorption (with peak concentrations at about 2 h after dosing). The elimination after dosing with aqueous solutions showed a marked similarity to the intravenous kinetics.
Keywords: distribution; food; inhalation toxicology; intravenous administration; pharmacokinetic model; pharmacokinetics; rat; styrene; styrene monomer; toxicology